Assessment of activation duration across the right ventricular outflow tract in patients with premature ventricular contractions using noninvasive electrocardiographic mapping: a validation study. (19th May 2022) - Parreira, A; Carmo, P; Marinheiro, R; Mesquita, D; Marques, L; Mancelos, S; Ferreira, A; Goncalves, A; Nunes, S; Chmelevsky, M; Ferreira, J; Coelho, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private hospital(s). Main funding source(s): Learning Health Introduction: Previous studies have reported that wavefront propagation speed across the right ventricular outflow tract (RVOT) can distinguish premature ventricular contractions (PVCs) with a RVOT origin from PVCs with a left ventricular outflow tract (LVOT) origin. Aim: Validate the non-invasive electrocardiographic mapping (ECGI) for assessment of RVOT activation duration (AD) during PVCs and assess its value as a predictor of the origin of the PVCs. Methods: We studied 18 consecutive patients, 8 males, median age 55 (35-63) years that underwent ablation of frequent (> 10.000 per 24 h) idiopathic PVCs with inferior axis, that had and an ECGI performed before ablation and the RVOT mapped in PVC. The ECGI was performed with the Amycard system, and invasive mapping was performed with the Carto or Ensite system. Isochronal activation maps of the RVOT in PVC were obtained with the activation direction method (ADM) of the ECGI, and with the Carto and Ensite systems. Total RVOT AD was measured as the time interval between the earliest and the latest activated region. Agreement between the two methods was performed using a Bland-Altman plot and linear regression . The cutoff value of AD to predict PVC origin was calculated with ROC curve. Results: PVCs originated from the RVOT in 11 (61%) patients. The median (Q1-Q3) RVOT AD measured with ECGI was 54 (39-68) ms and with invasive map 57 (36-70) ms. The agreement between both methods was good with an R2 of 0.747, p<0.0001. Figure displays the Bland-Altman plot (panel A), the linear regression plot (panel B). and two examples of the ECGI isochronal map (panel C). The AD was significantly higher in PVCs from the RVOT vs LVOT, both with ECGI and Carto, respectively 62 (58-73) vs 37 (33-40) ms, p<0.0001 and 68 (60-75) vs 34 (30-40) ms, p<0.0001. The cutoff value of 43 ms for AD measured with ECGI, predicted the origin of the PVCs with a sensitivity and specificity of 100%. Conclusions: We found good agreement between ECGI and Carto. The AD obtained with ECGI was accurate to predict the origin of the PVCs.